siMTA1-Loaded Exosomes Enhanced Chemotherapeutic Effect of Gemcitabine in Luminal-b Type Breast Cancer by Inhibition of EMT/HIF-α and Autophagy Pathways - Li, Pengping; Cao, Guodong; Huang, Yuqing; Wu, Wei; Chen, Bo; Wang, Zhenyu; Xiong, Maoming (Frontiers in Oncology, 2020)
Advanced breast cancer held a poor prognosis, for chemotherapy and endocrine therapy resistance. Autophagy is a main cause for tumor drug-therapy failure, and more evidence show EMT also is responsible for that. Metastasis-associated protein1 (MTA1) is up regulated in lots of tumors, which leads tumor progression and drug resistance. However, the role of MTA1 in chemotherapeutic resistance in luminal-b breast cancer is still unclear. In this paper, our research shows that higher expression of MTA1 accompanies with worse prognosis in luminal-b breast cancer. Knockdown of MTA1 enhances the sensitivity of MCF-7 to gemcitabine, and weakens metastasis ability of MCF-7 in vitro an in vivo. Following, we find that knockdown of MTA1 strengthens gemcitabine-mediated tumor growth inhibition effect in vivo, through reversion of the EMT process and inhibition of the autophagy process. Furthermore, our research builds the siMTA1-loaded exosomes, which increases the gemcitabine-mediated tumor growth inhibition effect in vivo.